Non-small-cell lung carcinoma: role of the Notch signaling pathway - Barse L (Dove Medical Press, 2015)
Levi Barse, Maurizio Bocchetta Department of Pathology, Oncology Institute, Loyola University Chicago, Maywood, IL, USA Abstract: Notch signaling plays a pivotal role during embryogenesis. It regulates three fundamental processes: lateral inhibition, boundary formation, and lineage specification. During post-natal life, Notch receptors and ligands control critical cell fate decisions both in compartments that are undergoing differentiation and in pluripotent progenitor cells. First recognized as a potent oncogene in certain lymphoblastic leukemias and mesothelium-derived tissue, the role of Notch signaling in epithelial, solid tumors has been far more controversial. The overall consequence of Notch signaling and which form of the Notch receptor drives malignancy in humans is deeply debated. Most likely, this is due to the high degree of context-dependent effects of Notch signaling. More recently, it has been discovered that Notch (especially Notch-1) can exert different, even opposite effects in the same tissue under differing microenvironmental conditions. Further complicating the understanding of Notch receptors is the recently discovered role for non-canonical Notch signaling. Additionally, the most frequent Notch signaling antagonists used in biological systems have been inhibitors of the transmembrane protease complex γ-secretase, which itself processes a plethora of class one transmembrane proteins and thus cannot be considered a Notch-specific upstream regulator. Here we review the available empirical evidence gathered in recent years concerning Notch receptors and ligands in non-small-cell lung carcinoma (NSCLC). Although an overview of the field reveals seemingly contradicting results, we propose that Notch signaling can be exploited as a therapeutic target in NSCLC and represents a promising complement to the current arsenal utilized to combat this malignancy, particularly in targeting NSCLC tissues under specific environmental conditions, such as hypoxia. Keywords: Notch-1, Notch-3, developmental signaling pathways, Notch inhibitors, NSCLC progenitor cells, CBF-1, MamL